2021
DOI: 10.1016/j.auec.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Emergency clinicians’ knowledge, preparedness and experiences of managing COVID-19 during the 2020 global pandemic in Australian healthcare settings

Abstract: Background Emergency clinicians have a crucial role during public health emergencies and have been at the frontline during the COVID-19 pandemic. This study examined the knowledge, preparedness and experiences of Australian emergency nurses, emergency physicians and paramedics in managing COVID-19. Methods A voluntary cross-sectional study of members of the College of Emergency Nursing Australasia, the Australasian College for Emergency Medicine, and the Australasian Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 57 publications
6
43
0
Order By: Relevance
“…Such findings have also been reported in our previous studies of other frontline healthcare workers in Australia, where clinicians reflected on their hardships of catching up with the most updated guidelines and protocols. (24)(25)(26)(27). Findings from an international, multi-site study reported that there was a lack of preparedness and/or confidence from general dentists with regard to implementation of infection prevention and control measures, and providing services to patients with confirmed/suspected COVID-19.…”
Section: It May Include the Provision Of Oral Health Or Treatment Information And Referral" (40)mentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings have also been reported in our previous studies of other frontline healthcare workers in Australia, where clinicians reflected on their hardships of catching up with the most updated guidelines and protocols. (24)(25)(26)(27). Findings from an international, multi-site study reported that there was a lack of preparedness and/or confidence from general dentists with regard to implementation of infection prevention and control measures, and providing services to patients with confirmed/suspected COVID-19.…”
Section: It May Include the Provision Of Oral Health Or Treatment Information And Referral" (40)mentioning
confidence: 99%
“…(8,23) Some studies identified and reported the learning experiences and knowledge acquisitions among frontline healthcare workers during the pandemic. (24)(25)(26)(27). We previously reported the knowledge, preparedness and experiences of Australian dentists during COVID-19 pandemic (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in accordance with previous research in which health care workers in designated COVID-19 hospitals perceived higher levels of discriminatory behaviours from the community [24] , [25] . COVID -19 was identified as a source of increased stress and anxiety for emergency clinicians in Australia and New Zealand with concerns about transmission of the disease to family members [16] , [26] . The direct influence of COVID-19-associated discrimination on ED staff is an important finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the knowledge, preparedness and experiences of emergency nurses and physicians 18 , paramedics 18 , general practitioners 19 , infectious diseases physicians 20 , infection control professionals 20 , and intensive care nurses 21 in managing the COVID-19 pandemic in Australian healthcare settings. This paper adds evidence regarding an additional professional craft group, namely dentists.…”
Section: Introductionmentioning
confidence: 99%